2013
DOI: 10.1097/hjh.0b013e3283643361
|View full text |Cite
|
Sign up to set email alerts
|

Differences between office and ambulatory blood pressures in children and adolescents attending a hospital hypertension clinic

Abstract: There is a common relation both in children and adults between OBP and ABP. It is only because high OBP is common in the elderly, and the lowest OBP is usually found in young children that large positive OBP-ABP differences have been associated with old age, and negative differences with childhood. OBP-ABP differences, often defined as white-coat effect, can have different directions and are likely to be largely due to regression to the mean.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
1
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 20 publications
2
23
1
2
Order By: Relevance
“…The higher ambulatory BP in normotensive children is reversed when monitoring hypertensives (61), a behaviour similar to that observed in the adult population, in which the difference between office and ambulatory BP gradually diminishes the lower is office BP, until for SBP values of about 120 mmHg also in adults ambulatory becomes higher than office BP (61.62). While the higher ambulatory than office BP in normotensive children has been attributed, at least in part, to physical activity, additional reasons may reside in the different method of measuring BP (61), the algorithm used to calculate systolic and DBP from the maximal amplitude (63), and the phenomenon of regression to the mean (61 The night-to-day BP ratio represents circadian variability due to the physiological nocturnal BP fall. Blood pressure normally decreases during the night-defined as 'dipping'.…”
Section: Ambulatory Blood Pressuresupporting
confidence: 62%
“…The higher ambulatory BP in normotensive children is reversed when monitoring hypertensives (61), a behaviour similar to that observed in the adult population, in which the difference between office and ambulatory BP gradually diminishes the lower is office BP, until for SBP values of about 120 mmHg also in adults ambulatory becomes higher than office BP (61.62). While the higher ambulatory than office BP in normotensive children has been attributed, at least in part, to physical activity, additional reasons may reside in the different method of measuring BP (61), the algorithm used to calculate systolic and DBP from the maximal amplitude (63), and the phenomenon of regression to the mean (61 The night-to-day BP ratio represents circadian variability due to the physiological nocturnal BP fall. Blood pressure normally decreases during the night-defined as 'dipping'.…”
Section: Ambulatory Blood Pressuresupporting
confidence: 62%
“…In this analysis, 162 pairs of duplicate OBP measurements obtained from 86 individuals showed a reasonable conformity of these oscillatory and auscultatory measurements, with oscillatory OBP overestimating systolic OBP by +1.5 mmHg and diastolic OBP by +0.8 mmHg on Bland Altman analysis. The conformity between oscillatory measurements (obtained by the same equipment used in the present study) and auscultatory measurements was also confirmed by Salice et al (15).…”
Section: Obp Measurementsupporting
confidence: 73%
“…31,40 The ELSA data confirm older findings Table. by guest on May 12, 2018 http://hyper.ahajournals.org/ Downloaded from that the WC effect is progressively lower the lower office BP is, 41 as well as the results of a recent study of normotensive and hypertensive children and adolescents showing the WC effect disappears and changes sign (ABP higher than office BP) at office BP values <110 to 120/65 to 70 mm Hg. 42 They also provide, however, additional information that previous studies, being noninterventional, could not provide. In the absence of treatment the relationship of the WC effect to office BP was much steeper in WCH than in SH individuals, and only the WCH curve steepness was reduced by treatment, whereas the SH curve steepness remained substantially unmodified.…”
Section: Discussionmentioning
confidence: 64%